Emergency Surgery for Acute Dissection of the Ascending Aorta - Alizadeh, Kambiz; Tabari, Masoomeh; Mohammadzadeh Tabrizi, Zohreh; Izanloo, Azra (Annals of Anesthesiology and Critical Care, 2016)
Background: Aortic dissection is a nonprevalent disease and its late diagnosis can be life-threatening with a high mortality rate. The timely treatment of this disease can increase the survival rate considerably. Objectives: The aim of this study was to provide a surgery report of patients with aortic dissection operated in a community hospital. Methods: In this descriptive study, the mortality rate and operation events of five patients with an acute aortic dissection referred to a community hospital were reported during the period of 2011 to 2015. Results: In this study, 5 patients with aortic dissection referred to the cardiology emergency ward of the hospital were operated. Twoof five patients were males; one of them had the Marfan’s disease and another one had the bicuspid aortic valve. The remainders were females; the first case was an old woman with a traumatic chest injury who died during the operation due to arrhythmia. The second case was a 42-year-old pregnant woman suspicious to Marfan’s disease with a history of sudden death in her brother. The third woman was a case of aneurysm of ascending aorta with a bicuspid aortic valve. Conclusions: The findings of this study show that early diagnosis and timely operation can increase the survival rate of patients with an aortic dissection.